Examining Internal Stakeholder Influence on Firm Sustainability: The Moderating Role of Organizational Support - Rachetty Hariprasad; Ashok Doraiswamy (Qubahan Academic Journal)
Sustainability is one of the trending topics everywhere. As per the United Nations Sustainable Development Goals (SDG), every developing and developed nation has to implement them. Due to this, many organizations are supposed to implement these practices, and in order to achieve this, employees play an important role. The main purpose of this study is to know how the environmental awareness of employees helps in achieving a firm’s sustainability under the moderating effect of organizational support. In this research, a structured questionnaire is prepared, and employees who are working in manufacturing and service sectors are considered for this study to fill out the questionnaire. 340 samples were collected and analyzed using PLS-SEM. Findings of the study reveal that organizational support doesn’t show much influence on employees concern for the environment. It is observed that the majority of the respondents have environmental concerns, and organizations are also giving sufficient training to their employees to follow sustainable practices within their organization as well as in their day-to-day activities.